Fine ceramics (advanced ceramics, advanced technical ceramics). Determination of bacterial reduction rate by semiconducting photocatalytic materials under indoor lighting environment. Semi-dry method for estimating antibacterial activity on the actual environmental bacteria contamination surface. (17th January 2020) - British Standards Institution,
No abstract available